Strategi Peningkatan Kualitas Tahfidz Al-Qur’an di Pondok Pesantren - Rokimin; Sofwan Manaf; Farhanuddin Siregar (Universitas Darunnajah Jakarta, Indonesia, 2023)
Abstract Tahfidz Al-Qur'an Islamic boarding school is an educational institution that emphasizes the importance of memorizing the Al-Qur'an. However, in this modern era, various challenges arise in efforts to maintain and improve the quality of tahfidz. This research aims to explore and analyze effective strategies that can be implemented in Islamic boarding schools to improve the quality of tahfidz Al-Qur'an. Through a qualitative approach, this research found that a combination of traditional teaching methods with modern technology, continuous training for teachers, a systematic curriculum, emotional and spiritual development of students, as well as improving learning facilities are the main keys in improving the quality of tahfidz. The research results show that (1). The strategy to improve the quality of tahfidz is to introduce several methods to the students, determine the memorization target, namely 3 juz per semester, establish good relationships with the students, hold simaan (2). Supporting factors for the quality of tahfidz are motivating students, tahfidz graduation, tahfidz exams, boarding school rules and regulations. The inhibiting factor is that students do not master makhraj letters and tajwid, and do not manage their time well. Alternating mushaf, physical and spiritual condition, good concentration, feeling lazy, no mentor and similar verses (3) efforts made to overcome obstacles are holding tahsin coaching, motivating students, Islamic boarding school rules and regulations, providing rewards and punishments. , absent the presence of supervisors, Establishing a standard memorized Qur'an. Keywords: Strategy, Tahfidz Quality, Pondok Tahfidz, Darunnajah Islamic Boarding School, Al-Qur'an